Chrysophanol Regulates Cell Death, Metastasis, and Reactive Oxygen Species Production in Oral Cancer Cell Lines. (26th May 2020) - Hsu, Po-Chih; Cheng, Ching-Feng; Hsieh, Po-Chun; Chen, Yi-Hsuan; Kuo, Chan-Yen; Sytwu, Huey-Kang
Abstract : Background . Oral cancer belongs to the class of head and neck cancers and can be life threatening if not diagnosed and treated early. Activation of cell death via apoptosis or reactive oxygen species (ROS) accumulation and inhibition of cell cycle progression, migration, and epithelial-to-mesenchymal transition (EMT) may be a good strategy to arrest the development of oral cancer. In this study, we analyzed the possible action of chrysophanol isolated from the rhizomes of Rheum palmatum on the oral cancer cell lines FaDu (human pharynx squamous cell carcinoma) and SAS (human tongue squamous carcinoma) by investigating whether chrysophanol could influence cell death. Method . Cell viability was measured by using the MTT assay. For the detection of apoptosis, terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) staining and subG1 population analysis were used. We also examined cell cycle progression and ROS levels by flow cytometry. Additionally, the expression of p53, p21, procaspase 3, cyclin D1, CDK4, cdc2, CDK2, E-cadherin, vimentin, and PCNA was evaluated by western blotting. Conclusion . Chrysophanol has an anticancer effect on FaDu and SAS cell lines. There is an increase in subG1 accumulation, ROS production, and cell cycle G1 arrest after treatment with chrysophanol. On the other hand, chrysophanol inhibited cell migration/metastasis and EMT. We proposed that chrysophanol may be a good candidate compound on oral cancer treatment in the further.